Role of Carbohydrate and Dietary Fiber for Soccer Players - Gaung Perwira Yustika (AKPER Dharma Wacana, 2018)
Soccer is the most well known and a phenomenal sport in the world, with around 270 million players registered to this game. Soccer has already attracted attention either sport scientist and government from many countries to promote the benefit of active physical activity and also maintained people’s health, including the minorities and poorest.. Furthermore, this sport can be used to support the health public program in order to prevent chronic diseases due to cause lack of physical activity.Quality food choices and adequate nutrition nutrient are important for supporting training program and enhancing the physical performance of professional athletes. Macronutrients provide the metabolic substrates necessary for producing the chemical energy required for skeletal muscle contraction and cardiovascular physiology, while the micronutrients help the metabolic reactions involved in energy production and gas transport in the circulation. Soccer is a sport requiring for both aerobic dominant and also anaerobic energy. It needs the players to exercise repetitively at high intensities using large muscle groups for periods of several seconds to several minutes for the full match (90 min) plus added time. Metabolically, athletes depend to a certain extent on their endogenous glycogen stores in the liver and skeletal muscles. Besides from genetic factor, talent and the effort of training, it has been acknowledged that no single factor plays a bigger role in maximaxing physical performance than dietary plan.This Review article was made to show the important role of carbohydrate and dietary fiber in the aspect of soccer game, resumed from scientific articles especially from Europe/USA where soccer was more advanced there. The writer hoped that this article written and published at Indonesia can be used to developed sport science and sport medicine for his beloved country.